INTERNET OF THINGS BASED REAL-TIME VITAL SIGN MONITORING SYSTEM USING MOBILE APPLICATION - Hadiyoso, Sugondo; Alfaruq, Akhmad; Tulloh, Rohmat; Rohmah, Yuyun Siti; Susanto, Erwin (Journal of Applied Engineering Science, 2021)
The development of telehealth technology in monitoring systems has been widely used to support applications in the health sector. The aim is to provide easy access for the community. One of the implications is a real-time monitoring system based on the Internet of Things (IoT) platform. Some health vital signs that are the focus of observation are ECG signal, SpO2, blood pressure and Heart rate which can provide heart health information. In this study an integrated system has been implemented, namely Vital Sign distributed monitoring system through the internet network. The implemented system was able to acquire vital sign then send data to the internet cloud to be stored and processed further for real-time monitoring needs by interested parties. An Android based application that was developed called iHealth VitalSign monitor capable of sending, processing and representing data in numerical and graphical forms. The average delay for each packet delivery was 154.73 ms and conform with the ITU-T recommendations for real-time data transfer. HR detection algorithms have been evaluated on real-time ECG signals, more than 2100 beats were tested and obtained an average accuracy of 98.78%. With this proposed application, it is hoped that it can increase the penetration of telehealth services.